A proteção jurídica do consumidor nos contratos de mútuo bancário e o direito à informação - França, Bruna Simões (2018)
The propose of this work is to analyze the right that the right that consumers have to be oriented and informed and the consequences of this right is not observed by the financial institutions especially in loan contracts and considering the vulnerability of the consumers. We will begin doing an explanation of the legal regime of the financial institutions on Brazilian Constitution, the Central Bank and the Monetary Authority, as well as the possibility for self-regulation. Then we will analyze the legal protection of the consumer in Brazil, with main focus on the information right. We will study the concept of good faith in legal terms and the responsibility of financial institutions in abusive loan contracts regarding consumers. There will be a highlight on de vulnerability of the consumer and de concept of consumers that are more vulnerable than others. This paper intends to demonstrate that loan contracts sign with disregard of the information right by the financial institution to not oblige the consumer. As a consequence of this violation, the contract should be considered as not valid and the parties involved must return to the previously situation